Investigating the role of aspirin on the mortality risk of sepsis-associated encephalopathy: a retrospective study - Huang, Fengzhen; Yi, Jiping; Li, Qiuli; Zhou, Tieqiao; Yue, Dongyou; Gong, Xiaoxiang; Meng, Heng (Frontiers in Neurology, 2025)
BackgroundSepsis-associated encephalopathy (SAE) is one of the most common complications of sepsis. Aspirin can serve as a promising therapeutic candidate and help improve patient outcomes in sepsis and its complications. However, the efficacy and safety of aspirin on SAE remains largely unexplored.MethodsPatients for this retrospective study were collected from MIMIC-IV (version 3.0). Propensity score matching (PSM) was used to balance the baseline characteristics between the no aspirin group and aspirin group. The association between aspirin therapy and mortality risk of in-hospital, 30-day, 60-day, 90-day, and 180-day was analyzed by Cox proportional hazards model and Kaplan–Meier method. E-value analysis was used to evaluate the potential influence of unmeasured or unknown confounding factors. Subgroup analysis was applied to explore potential differences in the effects of aspirin therapy on clinical outcomes across these various groups.ResultsOur study recruited 4,707 SAE patients in total, and 2,518 patients were enrolled after PSM. The mortality rate for in-hospital, 30-day, 60-day, 90-day, and 180-day in the aspirin group was consistently significant lower than that in the no aspirin group. Kaplan–Meier curves revealed that the SAE patients received aspirin therapy exhibited a notably higher survival rate compared to those who did not. The risk of gastrointestinal hemorrhage had no significant difference between the two groups. Additionally, the mortality rate of SAE patients in aspirin pre-ICU group, aspirin in-ICU group, and aspirin pre-ICU and in-ICU group decreased significantly compared to the no aspirin group. The high-dose aspirin group experienced a significantly higher mortality rate compared to those in the low-dose group.ConclusionAspirin could reduce the mortality risk of SAE patients for in-hospital, 30-day, 60-day, 90-day, and 180-day, without increasing the risk of gastrointestinal hemorrhage. The benefits observed persisted regardless of aspirin exposure timing. Patients received high-dose aspirin exhibited a higher mortality risk compared to those in the low-dose group.